Techniques and Quality of Ironic, Cynical, and Sarcastic Expressions in Ahmad Tohari’s Ronggeng Dukuh Paruk Trilogy Indonesian – English Translation - Wijayanti, Titik; Astuti, Puji; Hartono, Rudi (Universitas Negeri Semarang, 2021)
Many ironic, cynical, and sarcastic expressions are found in Ronggeng Dukuh Paruk trilogy. Because of the differences of situational context and cultural background, it is not easy for the target readers to grab the information and mission or messages delivered by Ahmad Tohari in the source text. Some techniques might be chosen by the translator. The accuracy, acceptability or naturalness, and readability of the ironic, cynical, and sarcastic expressions should also be considered. The aims of the study were first to identify the translation techniques of ironic, cynical, and sarcastic expression in Ronggeng Dukuh Paruk trilogy from Indonesian into English, and the second, to explore the translation accuracy, acceptability, and readability of translating ironic, cynical, and sarcastic expression in Ronggeng Dukuh Paruk trilogy from Indonesian into English. The object of this study was Ronggeng Dukuh Paruk trilogy written by Ahmad Tohari translated by Rene T.A. Lysloff. This study employed embedded research design. It combined or integrated qualitative and quantitative data. The data analysis was deductively built from particular to general. The result of the translation techniques analysis shows that the most dominant translation techniques are established equivalent, reduction, and modulation. Based on the analysis, it reveals that the translation quality of ironic expression translation possesses the highest score compared with cynic and sarcastic expressions translation. It can be concluded that translation techniques influence the translation quality. It might be suggested for the future researchers to investigate how translation technique influences the translation quality.